In the Gutter: Comix theory. Issue 1 (10th August 2012) - Gregory, Chase
Comix illustrate queerness, literally, both in the comics 'gutter' (the space between panels), and in the 'stutter' of the repeated frame. The gutter in comics makes clear that narrative can continue (in the form of reproductive futurity) only inasmuch as we continue to suture together gaps in narrative (the gaps of queer jouissance) through the 'imperative of figuration' and the compulsion to create meaning. The gutter and repetition stand in relation to deconstructionist ideas about the slippage inherent in meaning, but also have implications for our understanding of Lacanian orders (see David Ault's work on comics and Lacan). The comics medium, with its unique spatial/temporal relation, provides a visual metaphor for time, and in doing so offer ways for readers to envision time and space differently; because queerness is placed in opposition to institutions of linear time (family, heterosexual futurism, reproduction, capitalism), it challenges 'reproductive temporality' and instead posits new temporalities - ones that refuse forward movement through the institutions of generational inheritance and instead fuck with the family tree. Queer/comix temporalities fold back, repeat, stutter, and offer new ways of relating to time that are not driven by a reproductive imperative. In the literal illustration of the gutter/closure, the meaning/nonmeaning relation through the mechanisms of panel, gutter, and frame, comics make visible the queer element in all artistic media, and thus make visible the instability of any symbolic investment.